2020
DOI: 10.1002/cam4.3413
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of long‐term physical, emotional, and cognitive fatigue across 15 different cancer entities

Abstract: Background Fatigue prevalence and severity have been assessed in a variety of studies, yet, not in a standardized way, and predominantly in breast cancer patients. Systematic, comparative investigations across a broad range of cancer entities are lacking. Methods The FiX study systematically enrolled 2244 cancer patients across 15 entities approximately 2 years after diagnosis. Fatigue was assessed with the multidimensional EORTC QLQ‐FA12 questionnaire. Physical, emotional, cognitive, and total fatigue were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 29 publications
(53 reference statements)
1
22
0
Order By: Relevance
“… 30 As the patients in the study by Jellema et al were treated with conventional radiation therapy, the effect on fatigue is not entirely comparable to patients treated with parotid-sparing IMRT. For comparison with survivors of cancer with other cancer diagnoses, there is a recent study from Schmidt et al 31 in which they have assessed fatigue levels approximately 2 years after diagnosis with the EORTC QLQ-FA12 questionnaire. They analyzed 2,244 patients with 15 different cancer diagnoses (no patients with HNC included) and the mean values for all 3 dimensions (physical, emotional, and cognitive) are higher for all diagnoses compared with the scores in this present study.…”
Section: Discussionmentioning
confidence: 99%
“… 30 As the patients in the study by Jellema et al were treated with conventional radiation therapy, the effect on fatigue is not entirely comparable to patients treated with parotid-sparing IMRT. For comparison with survivors of cancer with other cancer diagnoses, there is a recent study from Schmidt et al 31 in which they have assessed fatigue levels approximately 2 years after diagnosis with the EORTC QLQ-FA12 questionnaire. They analyzed 2,244 patients with 15 different cancer diagnoses (no patients with HNC included) and the mean values for all 3 dimensions (physical, emotional, and cognitive) are higher for all diagnoses compared with the scores in this present study.…”
Section: Discussionmentioning
confidence: 99%
“…The subscale value for pain was even lower by more than 10 points in elderly HNSCC survivors than in the age- and gender-controlled general German population. While fatigue is a frequent long-term sequela for several cancer entities such as stomach, lung and breast cancer [ 26 , 27 ], it seems to be a less common patient-reported adverse event in surviving elderly HNSCC patients after (chemo)radiotherapy when comparing with the general population. In this context, it should be noted that most HNSCC patients adapt to their physical impairments such as xerostomia or dysphagia, leading to sometimes better global QoL values than physicians would assume.…”
Section: Discussionmentioning
confidence: 99%
“…For some interviews, insufficient time was available to discuss all disturbance ratings. Consequently, the number of individuals who mentioned a disturbance rating for an impact does not always equal the number of individuals who mentioned the impact BCLC Barcelona clinic liver cancer, HCC Research across cancer types has shown that fatigue is one of the most frequent and distressing symptoms of cancer and its treatment [36,37]. Consistent with these findings, in the current study, fatigue/lack of energy was identified across the various disease stages as being a particularly prevalent experience that individuals with HCC found highly disturbing.…”
Section: Discussionmentioning
confidence: 99%
“…Research across cancer types has shown that fatigue is one of the most frequent and distressing symptoms of cancer and its treatment [ 36 , 37 ]. Consistent with these findings, in the current study, fatigue/lack of energy was identified across the various disease stages as being a particularly prevalent experience that individuals with HCC found highly disturbing.…”
Section: Discussionmentioning
confidence: 99%